-3+11=-2z+3(z-2)

Simple and best practice solution for -3+11=-2z+3(z-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+11=-2z+3(z-2) equation:


Simplifying
-3 + 11 = -2z + 3(z + -2)

Combine like terms: -3 + 11 = 8
8 = -2z + 3(z + -2)

Reorder the terms:
8 = -2z + 3(-2 + z)
8 = -2z + (-2 * 3 + z * 3)
8 = -2z + (-6 + 3z)

Reorder the terms:
8 = -6 + -2z + 3z

Combine like terms: -2z + 3z = 1z
8 = -6 + 1z

Solving
8 = -6 + 1z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
8 + -1z = -6 + 1z + -1z

Combine like terms: 1z + -1z = 0
8 + -1z = -6 + 0
8 + -1z = -6

Add '-8' to each side of the equation.
8 + -8 + -1z = -6 + -8

Combine like terms: 8 + -8 = 0
0 + -1z = -6 + -8
-1z = -6 + -8

Combine like terms: -6 + -8 = -14
-1z = -14

Divide each side by '-1'.
z = 14

Simplifying
z = 14

See similar equations:

| -2A+8A-18+5A=-A+14-5A+2 | | 4x^2-16x+80=113 | | 2x+8=4x+11 | | 5x^2-11x-2=0 | | 16x-4y=32 | | 6(2a+7)=102 | | 10x^2-11x-2=0 | | 98b^2=2 | | (6r-3)(8r-3)= | | x-7=2x-3 | | 13+3x-9=10x-14-5x | | -9=108 | | 3x^2-3=45 | | x^2-24x+1=0 | | 100(x-3)=450-50 | | t/3-2=9 | | -6(8+6k)=-228 | | 7/5(40) | | x+7/5x=96 | | 6d/4=24 | | -153-12x=71+2x | | -5+7=5x-4(x-1) | | 9Y-1=y-5 | | D(3-7)-12=0 | | 6m/7-3=9 | | -82-3x=11x+170 | | 7m-10m=27 | | .5=.09 | | 9(w-4)=7w-44 | | 3+573g=3g | | 3+573=3g | | 3m^3-32m-8=0 |

Equations solver categories